Study of Estrogen Receptor-α and Receptor-β Gene Polymorphisms on Alzheimer's Disease - Goumidi, Louisa; Dahlman-Wright, Karin; Tapia-Paez, Isabel; Matsson, Hans; Pasquier, Florence; Amouyel, Philippe; Kere, Juha; Lambert, Jean-Charles; Meirhaeghe, Aline (Journal of Alzheimer's disease, 2011)
Estrogen treatment can modulate the risk for developing dementia in women. Therefore, single nucleotide polymorphisms (SNPs) in the estrogen receptor genes may constitute genetic susceptibility factors to Alzheimer's disease (AD). Thus, we investigated the impact of the genetic variability of the estrogen receptor α 1 (ESR1) and estrogen receptor α 2 (ESR2) genes on late onset AD risk. We analyzed 39 SNPs in ESR1 and 5 SNPs in ESR2 in a French case-control study of sporadic AD (1007 cases/647 controls). Individuals carrying the minor allele of rs7450824 had a lower risk of AD than homozygous subjects for the major allele (age, gender, and APOE ε4 allele adjusted odds ratio = 0.71 [0.57–0.89], p = 0.003). However, this association did not resist Bonferroni correction for multiple testing (p-threshold < 0.001). Consistently, no significant association could be detected when considering age of onset. We also tested for possible interactions between the ESR SNPs and APOE status (ε4 allele) or gender but no significant interaction could be observed. Even after stratifying the sample on APOE status or gender, no significant association with AD risk could be detected. Finally, we searched for potential gene-gene interactions between ESR1 and ESR2 SNPs but no significant interaction could be detected. Our results reinforce the notion that SNPs in the ESR1 or ESR2 genes do not seem to play a major role in the genetic susceptibility of AD.